Al-Attas’ Islamization of Science in Lakatosian Research Program Perspective - Amir Sahidin; Mohammad Muslih; Setiawan bin Lahuri (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2026)
This study addresses the growing development of the Islamization of Science concept proposed by Syed Muhammad Naquib Al-Attas, which has evolved into a scientific paradigm and gained significant scholarly support. However, despite its wide acceptance and extensive academic discourse, there remains a lack of studies examining Al-Attas’ Islamization from a rigorous methodological perspective for the development and advancement of scientific theories. Therefore, this study aims to analyze the Islamization of Science by Al-Attas from the perspective of the Lakatosian Research Program. This research employs a library research method with qualitative data and a philosophy of science approach. The findings reveal that, first, Al-Attas’ Islamization seeks to generate a new form of science integrated with religion; second, the stages of Islamization proposed by Al-Attas are closely aligned with Lakatosian Research Methodology, consisting of a hardcore in the form of worldview, a protective belt in the form of de-westernization, a series of theories through integration, and the creation of new science through Al-Attas’ purification process. In conclusion, Al-Attas’ Islamization of Science demonstrates a systematic and progressive structure that is methodologically compatible with the Lakatosian framework. This study contributes to strengthening the methodological foundation of the Islamization of Science and enriching the discourse of philosophy of science from an Islamic perspective.